2010
DOI: 10.1208/s12249-010-9408-x
|View full text |Cite
|
Sign up to set email alerts
|

Polymer Percolation Threshold in HPMC Extended Release Formulation of Carbamazepine and Verapamil HCl

Abstract: Abstract. The principles of the percolation theory were applied to further understand and design hydroxypropyl methylcellulose (HPMC) extended release matrix tablets containing carbamazepine and verapamil HCl. This statistical theory studies disordered or chaotic systems where the components are randomly distributed in a lattice. The application of this theory to study the hydration and drug release of hydrophilic matrices allows describing the changes in hydration and drug release kinetics of swellable matric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 17 publications
0
11
0
Order By: Relevance
“…As stated by percolation theory, a transitional change occurred at a critical concentration of components in a system when one component forms a cluster spreading throughout the whole system. This critical concentration, known as percolation threshold (Cp), is assigned to the volumetric ratio (% v/v) of the percolating component [13,14].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As stated by percolation theory, a transitional change occurred at a critical concentration of components in a system when one component forms a cluster spreading throughout the whole system. This critical concentration, known as percolation threshold (Cp), is assigned to the volumetric ratio (% v/v) of the percolating component [13,14].…”
Section: Discussionmentioning
confidence: 99%
“…It is considered as infinite or percolating cluster after this cluster spreads from one side to the other sides of the network. The concentration of a component that causes a maximum probability of appearance of a cluster of this component is named percolation threshold [13][14]. In terms of solid dosage form design, the critical concentration of disintegrant or percolation threshold of disintegrant is required to achieve the minimum disintegration time.…”
Section: Introductionmentioning
confidence: 99%
“…The Caraballo group suggested that rapid drug release below the percolation threshold may be related to the failure of matrices to develop an effective surface 'gel' barrier, one of the critical features controlling the drug release from HPMC matrices [14,30,31,38,40].…”
Section: The Effect Of Matrix Polymer Content On Gel Layer Developmentmentioning
confidence: 99%
“…For a percolating cluster to be formed, the material must be present at a concentration above the percolation threshold for that system. In the case of HPMC matrix tablets, it has been postulated that the HPMC when hydrated must be present in sufficient volume to form a cluster which percolates the whole matrix and results in the formation of a sufficiently controlling gel layer [31]. Below the polymer percolation threshold, the HPMC cannot form a percolating cluster and the matrix is less likely to have extended release properties [30].…”
Section: Introductionmentioning
confidence: 99%
“…3 shows the captopril release profiles from the HPMC matrices where there is a significant change in the release profiles between 5% and 10% w/w of HPMC K15M. Above 10% w/w of HPMC K15M (the polymer percolation threshold), an infinite cluster of this component is formed which is able to control the hydration and release rate (Gonçalves-Araújo et al, 2010). Above 25% w/w of HPMC K15M, the release rate does not decrease, which is usual in formulations of drugs that are highly soluble in water (Maderuelo et al, 2011).…”
Section: Drug Substance and Polymer Characterizationmentioning
confidence: 99%